2018
DOI: 10.1080/19420862.2018.1440164
|View full text |Cite
|
Sign up to set email alerts
|

An anti-TL1A antibody for the treatment of asthma and inflammatory bowel disease

Abstract: TL1A is an attractive therapeutic target for the treatment of mucosal inflammation associated with inflammatory bowel disease (IBD) and asthma. Blockade of the TL1A pathway has been shown to reduce inflammatory responses while leaving baseline immunity intact, and to be beneficial in animal models of colitis and asthma. Given the therapeutic potential of blocking this pathway in IBD and asthma, we developed C03V, a human antibody that binds with high affinity to soluble and membrane-bound TL1A. In an assay mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 29 publications
0
27
0
Order By: Relevance
“…In fact, some recent in vivo studies have reported that the anti-TL1A antibody reduces intestinal inflammation and fibrosis in murine colitis models. 28,29,30 This basic evidence indicates that anti-TL1A antibody could be effective for CD, especially for patients homozygous for the TL1A risk haplotype.…”
Section: Discussionmentioning
confidence: 88%
“…In fact, some recent in vivo studies have reported that the anti-TL1A antibody reduces intestinal inflammation and fibrosis in murine colitis models. 28,29,30 This basic evidence indicates that anti-TL1A antibody could be effective for CD, especially for patients homozygous for the TL1A risk haplotype.…”
Section: Discussionmentioning
confidence: 88%
“…IBD and asthma also share a common genetic susceptibility, which includes a polymorphism of gasdermin-B (GSDMB), a protein responsible for regulating differentiation and growth of epithelial cells [35], as well as a polymorphism for the Interleukine 23 receptor gene [36]. Furthermore, these two diseases seem to have a common therapeutic target, TL1A (part of the superfamily of tumor necrosis factor ligands), that, when inhibited by an anti-TL1A antibody, induces a reduction of the mucosal inflammation [37].…”
Section: Discussionmentioning
confidence: 99%
“…Several biological explanations have been proposed for the association between these two diseases. Among these are possible alterations of the microbiome [32,33], the 'hygiene hypothesis' according to which an increasing prevalence of immune-mediated diseases would be linked to a reduction of antigenic stimuli deriving from pathogens and environmental exposures during early childhood [34], as well as explanations linked to genetic susceptibility [35] and alterations of physiological inflammatory processes [36,37].…”
Section: Introductionmentioning
confidence: 99%
“…Risankizumab, targeting specifically IL-23, showed promising results in earlier clinical trials [108, 109]. One more recently described cytokine, TL1a, is involved in TNBS colitis and associated fibrosis and has recently been found to be a beneficial target in IBD models, including treatment of fibrosis [110]. PF-06480605, a TL1a targeting agent, is currently under clinical phase II evaluation (NCT02840721).…”
Section: Animal Models Of Ibdmentioning
confidence: 99%